Acceleration of charged particles by elliptic polarized waves of large amplitude - Buts, A.V.; Buts, V.A.; Kuzmin, V.V. (Вопросы атомной науки и техники, 2004)
In this paper the results of investigations on the charged particle dynamics in the homogeneous constant magnetic field and in the field of a flat wave of arbitrary intensity are presented. When the magnetic field is absent the particle trajectory is defined. It is shown, that a particle can be effectively drawn along the wave vector of the wave.
Average speed of this drawing is proportional to the square of the wave force parameter. The trajectories of particles
are significantly dependent on initial conditions. In the presence of constant external magnetic field the particles can
be effectively accelerated by the wave field. The particle dynamics is always chaotic if the wave force parameter is
enough large. This dynamic is characterized by the alternation. Викладені результаті дослідження динаміки заряджених часток у однорідному постійному магнітному
полі та в полі плоскої хвилі довільної напруженості. За відсутності постійного магнітного поля вигляд
траєкторії частки був визначений. Показано, що частка може ефективно захоплюватися полем зовнішньої
хвилі. Середня швидкість захоплення пропорційна квадрату параметру сили хвилі. При наявності
постійного магнітного поля. частки можуть ефективно прискорюватись полем хвилі. При великих
напруженостях поля динаміка часток завжди хаотична. Динаміка характеризується перемежністю. Изложены результаты исследования динамики заряженных частиц в однородном постоянном магнитном
поле и в поле плоской волны произвольной напряженности. В отсутствии магнитного поля определен вид
траектории частиц. Показано, что частицы могут эффективно увлекаться полем внешней волны. Средняя
скорость увлечения пропорциональна квадрату параметра силы волны. Вид траектории существенно зависит от начальных условий. При наличии постоянного магнитного поля частицы могут эффективно ускоряться полем волны. При больших напряженностях поля динамика частиц всегда хаотична. Динамика характеризуется перемежаемостью.